Drawing is Important for Your Child’s Development - Kamsidjo Budi Utomo (Universal Institute of Professional Management, 2020)
Child's growth and development is a parent's full attention, especially when the child is in the golden age. According to experts on mental development of children, 80 percent of children's brains develop in the golden age. So at that time, the role of parents is needed in monitoring the growth and development of children's brains. During the golden age the child's brain develops so quickly that any information will be absorbed, without seeing the information is good or bad. In addition to playing a role as a supervisor for the growth and development of children, parents must also be tasked with increasing knowledge, especially around child growth. One of the activities that can be trained to children in increasing knowledge while providing stimulus to the child's growth and development process is drawing. Connecting lines and joining dots in the pursuit of making a drawing requires a certain level of problem solving. In order for a child to consciously draw an object, they first need to visualize the shape and then work out the best way to reproduce it on paper. The problem-solving skills that children develop from drawing will also transfer over to other subjects like maths, where visual representations can often help in finding a solution.